Macroeconomic impact of value-added tax in Nepalese economy (Journal of Tikapur Multiple Campus, 2018)
The term 'Value Added Tax (VAT)' can be defined as a tax levied (on the value created) at each stage in the process of production and distribution of a good or service. These stages can be import, manufacturing, dealers, wholesalers and retailers etc. Value added tax (VAT) is a tax on the value that a business firm adds to the things it buys from other firms in producing its own product. The main objective of this study is to assess the impact of VAT on GDP, PCON, IMP, GE, GNS, TI and to examine the relationship and causality among the macro economic variables. In model specification only few variables such as Gross Domestic production (GDP), value added tax (VAT), private consumption (PCON), import (IMP), government expenditure (GE), gross national saving (GNS) and total investment (TI) are including many other variables are unable to include. Literature review suggests a growing need for examining extensive study on the contribution of VAT on economic growth. There is lack of macro level studies ascertaining the impact of VAT in economic growth and moreover this study incorporate more important variables as like private consumption, import, government expenditure, gross national saving, disposable personal income and total investment in the study. Some important findings have been obtained. The econometrics results have shown the fact that a positively significant impact of VAT on gross GDP of a country (Model I). Regarding the relationship between private consumption, disposable personal income, value added tax( model 1.4), import, nominal gross domestic production, value added tax (model 1.5), government expenditure, nominal gross domestic production, value added tax(model 1.6), gross national saving , nominal gross domestic production, value added tax(model 1.7), The application of VAR to examine the long run relationship suggest long run relationship and all the explanatory variables are statistically insignificant but all the model are free from the autocorrelation, Heteroskedasticity and residuals are normally distributed which is desirable. There is unidirectional granger cause as like LnGDP to LnVAT, LnGDP to LnGNS and LnTI to LnGDP.